De novo tacrolimus extended‐release tablets (LCPT) versus twice‐daily tacrolimus in adult heart transplantation: Results of a single‐center non‐inferiority matched control trial. Issue 12 (1st October 2021) - van Zyl, Johanna S.; Sam, Teena; Clark, Donna M.; Felius, Joost; Doss, Amanda K.; Kerlee, Kacie R.; Cheung, Zi‐On; Martits‐Chalangari, Katalin; Jamil, Aayla K.; Carey, Sandra A.; Gottlieb, Robert L.; Guerrero‐Miranda, Cesar Y.; et al.
Abstract: Extended‐release tacrolimus for prophylaxis of allograft rejection in orthotopic heart transplant (OHT) recipients is currently not FDA‐approved. One such extended‐release formulation of tacrolimus known as LCPT allows once‐daily dosing and improves bioavailability compared to immediate‐release tacrolimus (IR‐tacrolimus). We compared the efficacy and safety of LCPT to IR‐tacrolimus applied de novo in adult OHT recipients. Twenty‐five prospective recipients on LCPT at our center from 2017 to 2019 were matched 1:2 with historical control recipients treated with IR‐tacrolimus based on age, gender, and baseline creatinine. The primary composite outcome of death, acute cellular rejection, and/or new graft dysfunction within 1 year was compared using non‐inferiority analysis. LCPT demonstrated non‐inferiority to IR‐tacrolimus, with a primary outcome risk reduction of 20% (90% CI: ‐40%, ‐.5%; non‐inferiority P  = .001). Tacrolimus trough levels peaked at 2–3 months and were higher in LCPT (median 14.5 vs. 12.7 ng/ml; P  = .03) with similar dose levels (LCPT vs. IR‐tacrolimus: .08 vs. .09 mg/kg/day; P  = .33). Cardiovascular‐related readmissions were reduced by 62% ( P  = .046) in LCPT patients. The complication rate per transplant admission and all‐cause readmission rate did not differ significantly. These results suggest that LCPT is non‐inferior in efficacy to IR‐tacrolimus with a similar safety profile and improved bioavailability in OHT.